2019
DOI: 10.1161/atvbaha.119.312705
|View full text |Cite
|
Sign up to set email alerts
|

Atherosclerosis in Chronic Kidney Disease

Abstract: Patients with chronic kidney disease (CKD) are at an increased risk of premature mortality, mainly from cardiovascular causes. The association between CKD on hemodialysis and accelerated atherosclerosis was described >40 years ago. However, more recently, it has been suggested that the increase in atherosclerosis risk is actually observed in early CKD stages, remaining stable thereafter. In this regard, interventions targeting the pathogenesis of atherosclerosis, such as statins, successful in the general p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
166
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 208 publications
(169 citation statements)
references
References 295 publications
2
166
0
1
Order By: Relevance
“…It is suggested that fluid overload and increased arterial stiffness play a role in LVH even before the start of dialysis therapy [15]. Arteriosclerosis, being a hallmark of arterial remodeling in ESRD, is characterized by diffuse calcification in combination with dilatation, and an increased wall thickness of the medial layer of the aorta and its main branches which drives increased arterial stiffness [11,16,17]. Here, LVH happens regardless of the effective control of hypertension.…”
Section: Left Ventricular Cardiomyopathymentioning
confidence: 99%
“…It is suggested that fluid overload and increased arterial stiffness play a role in LVH even before the start of dialysis therapy [15]. Arteriosclerosis, being a hallmark of arterial remodeling in ESRD, is characterized by diffuse calcification in combination with dilatation, and an increased wall thickness of the medial layer of the aorta and its main branches which drives increased arterial stiffness [11,16,17]. Here, LVH happens regardless of the effective control of hypertension.…”
Section: Left Ventricular Cardiomyopathymentioning
confidence: 99%
“…Recent evidence shows that there is a high prevalence of vascular calcification (VC) in atherosclerosis, diabetes, and chronic kidney disease, standing out as an independent CRF of morbidity and mortality [2,3]. Data from the MESA study show that the calcium score (CAC), the main marker of CV, was associated with a gradual increase in risk events.…”
Section: Introductionmentioning
confidence: 99%
“…1 Various factors including uremic toxins, oxidative stress, diabetes mellitus, hypertension, and dyslipidemia have been considered to be responsible for progression of atherosclerosis in CKD patients. 2 Atherosclerosis contributes to the development of cardiovascular diseases including coronary artery disease and stroke, which are common causes of death in CKD patients. 3 Therefore, assessment of subclinical atherosclerosis is important for preventing the development and progression of cardiovascular disease.…”
Section: Introductionmentioning
confidence: 99%